Psychiatric disorder and work life: A longitudinal study of intra-generational social mobility. (March 2016) - Tiikkaja, Sanna; Sandin, Sven; Hultman, Christina M; Modin, Bitte; Malki, Ninoa; Sparén, Pär
Background: Intra-generational social mobility, which describes the mobility within an individual's own working life, is seldom studied among employees with psychiatric disorders (EPD). There is need of knowledge of the intra-generational mobility patterns, in a broader perspective, among EPD. Aims: To investigate intra-generational social mobility in employed individuals diagnosed with affective disorder, personality disorder, schizophrenia and drug dependence in a national Swedish cohort. Method: We identified a national sample of employed Swedish adults born in 1939–1949 ( N = 876, 738), and among them individuals with a first-time hospital admission for affective psychosis, neurosis and personality disorder, alcoholism, drug dependence or schizophrenia in 1964–1980 ( N = 18, 998). Employed individuals without hospital admission for such diagnoses were utilised as a comparison group ( N = 866, 442). Intra-individual social class changes between 1980 and 1990 among EPD and the comparison group were described through summary statistics and graphs. Results: EPD more often held Low manual occupations at baseline in 1980 than the comparison group (44% vs. 28%), although parental social class was similar. In 1990, 19% of EPD and 4% of the comparison group had lost contact with the labour market. Social stability was less common among EPD (49 %) than in the comparison group (67%). Mobility out of the labour force increased and social stability decreased by number of inpatient admissions. Employees diagnosed with affective psychosis or neurosis and personality disorder fared better in the labour market than employees with schizophrenia. Conclusion: Employees suffering from psychiatric disorder do not maintain their social class or remain in the labour force to the same extent as individuals without those problems, irrespective of their parental class. Our results support the social drift hypothesis that individuals with poor psychiatric health move downward in the social hierarchy.